On an Incorrect Consistent Mass Matrix Formulation in the Dynamics of Trusses - Olszowski, B. (Engineering Transactions, 1991)
In the recent bibliography of FEM applications in structural dynamics one can find an erroneous formulation of consistent mass matrix for truss-type element. The aim of the paper is to correct this formulation, to discuss the errors and to present the accurate values of eigenfrequencies computed for some selected types of plane trusses.